The relationship between intensity and stochastic matrices for continuous-time discrete value stochastic non-homogeneous processes with Markov property - Sokol, Mi los lawa (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
The matrices of non-homogeneous Markov processes consist of time-dependent functions whose values at time form typical intensity matrices. For solvingsome problems they must be changed into stochastic matrices. A stochas-tic matrix for non-homogeneous Markov process consists of time-dependent functions, whose values are probabilities and it depend on assumed time pe- riod. In this paper formulas for these functions are derived. Although the formula is not simple, it allows proving some theorems for Markov stochastic processes, well known for homogeneous processes, but for non-homogeneous ones the proofs of them turned out shorter.